(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
A thorough assessment of diversity combining methods, including Equal Gain Combining (EGC), Selection Combining (SC), and Maximal Ratio Combining (MRC), in wireless communication systems exposed to independent Rayleigh and Rician fading channels is presented in this work. Using Quadrature Phase Shift Keying (QPSK) modulation, the performance is examined. Rayleigh and Rician fading environments are generated as part of a comprehensive system model that is designed and simulated to represent realistic multipath propagation conditions. Every diversity plan is put into place to lessen the effect that fading has on signal integrity. The performance of each method is then evaluated by computing the Bit Error Rate (BER) at different Signal-to-Noise Ratio (SNR) levels. According to simulation results, EGC provides a performance that is comparable to MRC with less complexity, whereas MRC consistently achieves the lowest BER thanks to its ideal signal-to-noise ratio gain. Even though SC is the most straightforward, its inferior branch selection results in a higher BER. The study underscores the trade-offs between complexity and performance in diversity combining techniques and affirms the superiority of MRC in enhancing QPSK signal robustness under both Rayleigh and Rician fading conditions.